1993
DOI: 10.1016/0270-9139(93)90465-y
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptors and heat-shock proteins in patients with primary biliary cirrhosis

Abstract: Primary biliary cirrhosis has a definite female preponderance. Increased estrogen levels have been found in patients with this disease; however no studies indicate the status of sex hormone steroid receptors in primary biliary cirrhosis patients. In this study the occurrence and distribution of estrogen receptors, progesterone receptors and androgen receptors in liver biopsy specimens from patients with primary biliary cirrhosis were examined and compared with these receptors in the normal liver. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Supporting our findings, a number of studies have shown the presence of functional ARs in liver cells, including hepatocytes and bile ducts from PBC patients (26,29,38). Also, the AR mRNA has been detected in human liver biopsy samples, fetal liver, and HepG2 cells (48).…”
Section: Discussionsupporting
confidence: 88%
“…Supporting our findings, a number of studies have shown the presence of functional ARs in liver cells, including hepatocytes and bile ducts from PBC patients (26,29,38). Also, the AR mRNA has been detected in human liver biopsy samples, fetal liver, and HepG2 cells (48).…”
Section: Discussionsupporting
confidence: 88%
“…1B). Low-level expression of the progesterone receptor was expected in hepatocytes (36). Similarly, progesterone receptors (PR, PGRMC1, and PGRMC2) were expressed by male NRC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bar ϭ 20 m. B: immunohistochemistry for progesterone receptors (PR, PGRMC1, and PGRMC2) in liver secretion from normal and BDL female male rats confirms receptor expression by bile ducts. Low-level expression of the progesterone receptor was expected in hepatocytes (36). C: by immunofluorescence, progesterone receptors (PR, PGRMC1, and PGRMC2) were expressed by normal rat intrahepatic cholangiocyte cultures (NRC).…”
Section: Methodsmentioning
confidence: 99%
“…Virtually all living organisms display this characteristic pattern of protein synthesis to diverse stimuli including alcohols, free radicals, glucose starvation, heavy metals, hypoxia, fevers and inflammation. Thus, heat-shock proteins are now more commonly called stress proteins (2,3). This editorial will first present an overview of the biological roles of several classes of stress proteins and will consider the increasingly persuasive evidence of their potential clinical relevance in aging, cancer, cardiovascular disease and autoimmunity (3).…”
mentioning
confidence: 99%